The methyltransferase EZH2 is not required for mammary cancer development, although high EZH2 and low H3K27me3 correlate with poor prognosis of ER‐positive breast cancers - Woo Kyun Bae; Kyung Hyun Yoo; Ji Shin Lee; Young Ho Kim; Ik‐Joo Chung; Min Ho Park; Jung Han Yoon; Priscilla A. Furth; Lothar Hennighausen (2014)
ABSTRACT Enhancer of zeste homolog 2 (EZH2) catalyzes trimethylation of histone H3 lysine 27 (H3K27me3) and its demethylation is catalyzed by UTX. EZH2 levels are frequently elevated in breast cancer and have been proposed to control gene expression through regulating repressive H3K27me3 marks. However, it is not fully established whether breast cancers with different levels of H3K27me3, EZH2 and UTX exhibit different biological behaviors. Levels of H3K27me3, EZH2 and UTX and their prognostic significance were evaluated in 146 cases of breast cancer. H3K27me3 levels were higher in HER2‐negative samples. EZH2 expression was higher in cancers that were LN+, size > 20mm, and with higher tumor grade and stage. Using a Cox regression model, H3K27me3 levels and EZH2 expression were identified as independent prognostic factors for overall survival for all the breast cancers studied as well as the ER‐positive subgroup. The combination of low H3K27me3 and high EZH2 expression levels were significantly associated with shorter survival. UTX expression was not significantly associated with prognosis and there were no correlations between H3K27me3 levels and EZH2/UTX expression. To determine if EZH2 is required to establish H3K27me3 marks in mammary cancer, Brca1 and Ezh2 were deleted in mammary stem cells in mice. Brca1‐ deficient mammary cancers with unaltered H3K27me3 levels developed in the absence of EZH2, demonstrating that EZH2 is not a mandatory H3K27 methyltransferase in mammary neoplasia and providing genetic evidence for biological independence between H3K27me3 and EZH2 in this tissue. © 2014 Wiley Periodicals, Inc.